Institutionalization and adoption of digital technology in Thai maritime industry - Janmethakulwat, Atcharaporn; Thanasopon, Bundit (My University, 2025)
Purpose This study explores the complex process of digital technology adoption and institutionalization within the Thai maritime industry. It aims to discern the pivotal factors that influence the integration of digital technologies into organizational practices, focusing on members of the Thai Shipowners Association (TSA). Design/methodology/approach This study integrates the technology organization and environment (TOE) framework, technology acceptance model (TAM) and institutional theory to investigate digital technology adoption in the Thai maritime industry. A survey was distributed to all shipowners in the TSA, achieving a 22% response rate with 240 valid responses from an estimated 1,100 employees. Data were analyzed using partial least squares-structural equation modeling (PLS-SEM). Findings Key findings of the research include the identification of IT skills and IT support as strong predictors of perceived ease of use, while organizational culture and top management endorsement significantly influence perceived benefits. The study also highlights the less definitive impact of organizational rules and legal requirements on adoption intentions. A notable insight is the role of social pressure in driving institutional changes, emphasizing the importance of external influences in technology integration. Research limitations/implications This study’s primary limitation is its context-specific focus on Thai maritime companies, which may not generalize to other industries or cultural contexts. Findings could vary under different organizational conditions or regulatory frameworks. Additionally, some results, such as the non-significant impacts of reliable IT infrastructure and legal frameworks, suggest complexities in technology adoption and institutionalization not fully captured by the study. Future research should expand these findings across diverse industries and explore how evolving digital technologies influence organizational strategies. Originality/value This research contributes uniquely by deploying an integrative theoretical model to examine digital technology adoption in an industry that is traditionally slow to innovate. The findings offer substantial insights into the processes of adoption and institutionalization, demonstrating how these contribute to long-term operational improvements in maritime businesses. This dual focus is instrumental for stakeholders aiming to navigate the complexities of digital transformation effectively.
Keywords: Digital technology; Institutionalization; Maritime industry; Technology adoption